Promoting the documentary heritage in the digital age: the BRGM's experience in Africa - (:unkn) unknown (My University, 2016)
Geoscience knowledge in Africa, compiled and produced by BRGM for over a century, initially indispensable for exploring the continent's natural resources, is likewise being exploited today under programs aimed at reinforcing the geological and mining infrastructures of African nations.
Keywords: African Research